2021
DOI: 10.3389/fneur.2021.634065
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Apraxia of Speech and Aphasia in Patients With Hand Motor Impairment After Stroke

Abstract: Objective: Aphasia and apraxia of speech (AOS) after stroke frequently co-occur with a hand motor impairment but few studies have investigated stroke recovery across motor and speech-language domains. In this study, we set out to test the shared recovery hypothesis. We aimed to (1) describe the prevalence of AOS and aphasia in subacute stroke patients with a hand motor impairment and (2) to compare recovery across speech-language and hand motor domains. In addition, we also explored factors predicting recovery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…Hybbinette et al [ 27 ] confirmed the common occurrence of apraxia of speech and aphasia in left hemisphere stroke patients with a hand motor impairment through a small sample study. Our correlation analyses results show that the four dimensions of language function—spontaneous speech, comprehension, repetition, and naming—were all associated with UE motor status (see Figure 5 ).…”
Section: Discussionmentioning
confidence: 95%
“…Hybbinette et al [ 27 ] confirmed the common occurrence of apraxia of speech and aphasia in left hemisphere stroke patients with a hand motor impairment through a small sample study. Our correlation analyses results show that the four dimensions of language function—spontaneous speech, comprehension, repetition, and naming—were all associated with UE motor status (see Figure 5 ).…”
Section: Discussionmentioning
confidence: 95%
“…This finding could be due to the fact that upper limb movements and speech are developed from adjoining areas of the brain and shares common anatomical network. 6,14,16 Furthermore, this result permits a possibility that recovery of arm function and speech follows a parallel approach.…”
Section: Resultsmentioning
confidence: 90%
“…They also concluded that recovery of speech-language and motor domains follows a parallel path, despite of severity, supporting the common recovery hypothesis that similar brain recovery mechanisms are involved in speech-language and motor recovery post stroke. 6 However, few other studies contradicted this statement by concluding that there are no anatomical association among arm functions and language. 16 The present study was done to find the association between recovery of language and upper extremity function in post stroke patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar effect was also found following transcranial direct current stimulation over the motor cortex, which led to improved language outcomes (Meinzer et al, 2016 ). More recently, Hybbinette et al also demonstrated that similar mechanism of recovery may be involved in language and motor recovery post-stroke, further contributing to the so-termed “shared recovery hypothesis” (Hybbinette et al, 2021 ). While well-controlled studies examining this phenomenon are lacking, our findings may suggest either: functional compensation by the language system associated with better performance, or impaired connectivity within the language system manifesting in poor sensorimotor outcomes.…”
Section: Discussionmentioning
confidence: 98%